How do peer networks support people with personal budgets? A review of the research evidence from the United Kingdom. Issue 1 (2nd January 2020) - Hyslop, Jon; Aveyard, Helen; de Abreu, Guida; Appleton, Jane V.
Abstract: This literature review was conducted to describe the range of organisations and informal groups providing peer support to personal budget users in the United Kingdom between the launch of direct payments in 1997 and 2016. Forty-five research reports included relevant evidence. This has been aggregated to show how peer networks supported individual users, as well as to describe their wider role in policy development and implementation. Despite their diversity, the support they provided often had common characteristics. Peer networks fostered collaboration, enhanced communication, built confidence amongst people who were entitled to a personal budget, and applied specialist knowledge that was often derived from the lived experience of network members. None of these characteristics was exclusive to peer networks. However, they may have been more deeply culturally embedded here than in other settings, which perhaps accounts for the positive experiences of support reported in the research literature. Points of interest: It is now more than 20 years since direct payments first enabled UK residents to take the money used to pay for their social services as personal budgets. Early research showed that support provided through peer networks including disabled people's organisations had particular advantages. Despite this, the proportion of support commissioned from peer networks has subsequently reduced. This review of the research literature details the helpful support provided by peer networks at each stage of obtaining and managing a personal budget. The approaches taken by peer networks were often innovative and original, and this article summarises their characteristics.